2003
DOI: 10.1002/cncr.11118
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic linear accelerater‐based radiosurgery for the treatment of patients with glomus jugulare tumors

Abstract: Activated layered double hydroxides (LDHs) with high crystallinity, obtained by calcination/rehydration of LDH precursors synthesized by urea decomposition, have higher catalytic activity in acetone self‐condensation and Knoevenagel reactions than less crystalline materials obtained from LDH precursors synthesized by titration co‐precipitation. The activated LDHs possess both basic and acidic sites. High resolution transmission electron microscopy (HRTEM) confirms that the highly crystalline activated LDHs ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 32 publications
1
50
0
Order By: Relevance
“…4 With the advent of improved microsurgical techniques and the use of combined approaches, the mortality rate has lowered substantially; however, cranial nerve injury continues to be a problem. [18][19][20][21] In a retrospective series of 176 patients treated between 1972 and 1998 and reported by Jackson, et al, 12 in 85% complete surgical control was described. The remaining 15% of their patients had a subtotal resection or recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 With the advent of improved microsurgical techniques and the use of combined approaches, the mortality rate has lowered substantially; however, cranial nerve injury continues to be a problem. [18][19][20][21] In a retrospective series of 176 patients treated between 1972 and 1998 and reported by Jackson, et al, 12 in 85% complete surgical control was described. The remaining 15% of their patients had a subtotal resection or recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, their patient numbers were small. In a more recent series by Maarouf, et al, 19 the authors reported their experience with LINAC therapy in 12 patients with glomus jugulare tumors. In their study the median dose was 15 Gy and the median follow-up period was 4 years.…”
Section: Neurosurg Focus / Volume 17 / August 2004mentioning
confidence: 99%
“…[ 83 ]. Should re-operation not be possible, high-dose particle beam therapy or IMRT should be recommended Embolization alone does not prevent further tumor progression [ 92 ]. Surgical resection is the only treatment option that can offer immediate and complete tumor elimination.…”
Section: Rationale For Treatment and Alternativesmentioning
confidence: 98%
“…Poznanovic et al 36 published a series report in which 8 patients received LINAC treatment for glomus jugulare, and all patients exhibited tumor control and clinical stability over an average follow-up time of 15.6 months. Maarouf et al 25 followed 12 patients who received LINAC treatment for glomus jugulare for a median duration of 48 months. Although no tumors increased in size (80% regressed and 20% remained unchanged), 8 improved clinically and 4 worsened.…”
Section: Radiosurgical Treatmentmentioning
confidence: 99%